Work Incentives for “Welfare Mothers” in 1970s Ontario: Screening Out the Political - McKeen, Wendy (Labour / Le Travail, 2020)
This article analyzes the politics surrounding the 1970s/early 1980s introduction of work-incentive measures for “welfare mothers” in Ontario. It uses governance and assemblage theory to analyze the substance and dynamics of the debates in this area as they involved state officials, social policy and social welfare advocates, and welfare mother activists. Using a wide array of archival documents and media accounts, the article uncovers the discursive and other kinds of practices that government officials used in seeking to contain the debate and foreclose more radical possibilities, as well as the role that progressive groups sometimes played in reinforcing official expertise. The article concludes that the work incentives for welfare mothers measures were not just benign policy but mechanisms that screened out the political and, ultimately, further disempowered and marginalized welfare mothers. Such programs operate to this day to reinforce a worldview that ignores structural oppression and inequality.